Reprisal Actions of Partisans in Kaunas County (1944–1952), Part 1 - Miknevičius, Gintautas (Genocidas ir rezistencija, 2019)
This research focuses on the punitive operations of Lithuanian partisans in Kaunas County. The data covers the voloks that belonged to Kaunas County before the administrative-territorial reform of 1946, after which the territory of the county changed. During the administrative-territorial reform of 1950, instead of the abolished voloks, regions and districts were formed, so there may be some inaccuracies in the attribution of the dead to Kaunas County, but they are minor, as the partisans did not actually carry out punitive operations from 1950 on. The number of casualties between 1950 and 1952 is very small and does not affect this research. All violent deaths are investigated. The research aimed to find out which cases were partisan actions and which were criminal offences attributed to the partisans during the Soviet era.